Determining the Economic Value of Offshore Wind Power Plants in the Changing Energy System. (2015) - Richts, Christoph; Jansen, Malte; Siefert, Malte
Abstract: This paper analyses the economic effect of integrating large offshore wind energy capacities in the German future energy system. For this purpose three scenarios are compared at a completed transformation status in which 80% of Germany's final energy consumption (electricity, heat and transportation) is provided by renewable energy systems (RES). Emphasis is put towards an overall system perspective accounting for generation costs of renewable energy sources and balancing requirements of renewables (flexibility costs). A second focal point is the analysis of relevant power plant properties of offshore wind power, especially the provision of control reserve power.